Regional Differences Illustrated by Registered Unemployment Maps with Natural Intervals Jenks at Local Administrative Units LAU 2 Level (NUTS 5) in Romania - Lincaru, Cristina; Ciucă, Vasilica; Atanasiu, Draga; Drăgoiu, Codruța (Calitatea Vieții, 2015)
In this article are illustrated the regional differences on the issues and characteristics of registered unemployment as an operational example for a socio-economic indicator, relevant for the cohesion policy. Regional differences are illustrated by “Choropleth Map” of registered unemployment classified by natural intervals Jenks at local administrative units LAU 2 (NUTS 5) in Romania, the finest level of administrative detail. By applying dasymetric detailing the values recorded at NUTS 3 level to NUTS 5 level was diminished the ecological error. We analyse extensive type indicators as it is the number of registered unemployed in 2013 and the end of June 2014, and intensive type indicators as it is the number of unemployed densities per km2 in 2013 and in June 2014. The classification technique used was the natural intervals Jenks the Arc Gis 10.2, with data provided by INS TEMPO data base. These researches results have been achieved in the Project Nucleu NP – 420115, Phase 3: Regional differences on Labour market, made in 2014, and results are used in Dynahu Project.